Monopoly in Malaysia television market: Effect on Malaysian film producers - Zairul Anuar Md. Dawam; Rosli Sareya; Addley Bromeo Bianus; M Fazmi Hisham; Shahizan Ali (Maya Global Education Society, 2015)
The emergence of television in Malaysia has created new market opportunity for local production companies to sell products or television shows they have produced. Television has now become a bigger market compared to the film market for cinema screening. This is contributed by the increasing number of television channels in Malaysia which has eight free television channels i.e. TV1, TV2, TVi, TV3, NTV7, 8TV, TV9 and TV Al-Hijrah. Paid television network named ASTRO satellite television which serves more than 170 television channels has also provided new market opportunity through the channels of Astro Ria, Astro Prima and Astro Mustika. ASTRO also provides market opportunity for producers to broadcast recent films premiered in cinema through the pay per view channel known as Astro First. However, the ownership of television channels by particular company is feared to prompt monopoly in television market. This article discusses the effect on Malaysian film producers or production companies in Malaysia television market. Among issues being discussed are procedure to purchase television programme by government television network i.e. Radio dan Televisyen Malaysia (RTM), issue of low price purchase, ownership of products copyright by private television network and continually increment in subscription price by the first satellite television in Malaysia, ASTRO.